Associations between childhood exposure to community violence, child maltreatment and school outcomes. (June 2020) - Schneider, Samantha
Abstract: Objectives: This study examined whether physical abuse and community violence exposure (CVE) at age 5 were independently associated with academic performance at age 9, whether these effects were mediated by externalizing and internalizing behaviors, and whether the effects of CVE on mental health and academic performance were observed after accounting for the effects of physical abuse. Methods: Data were drawn from the Fragile Families and Child Wellbeing Study. Bayesian factor analysis was conducted in Mplus to form latent factors for internalizing behavior, externalizing behavior, and academic performance. Path analysis was then used to examine direct and indirect associations between CVE, internalizing and externalizing behaviors, and academic performance. Results: CVE at age 5 was independently negatively associated with academic performance at age 9. Physical abuse at age 5 was not independently associated with academic performance at age 9. The effects of CVE and physical abuse on academic performance were mediated by externalizing behavior, and not internalizing behavior. CVE, externalizing behavior, and internalizing behavior all had a direct negative association with academic performance, after accounting for the effects of physical abuse on externalizing behavior. Conclusions and Implications: The findings confirmed that community violence has a negative impact on school performance above and beyond the effects of interpersonal violence. These findings reinforce the need for communitywide prevention programs that reduce violence. These findings suggest that more attention needs to be paid to how younger children are impacted by CVE and physical abuse, both through their own experiences or the experiences of their caregivers.